Ultrafast and low-temperature synthesis of patternable MoS2 using laser irradiation. (27th February 2019) - Jung, Jaehyuck; Lee, Jinhwan; Kim, Youngchan; Bark, Hunyoung; Lee, Changgu
Abstract: The fascinating properties of transition metal dichalcogenides have been studied for a decade to broaden their promising applications as flexible electronics. However, conventional mass production of 2D materials is carried out at relatively high temperatures over 600 °C, which typical flexible substrates cannot withstand. For this reason, proper low-temperature synthesis methods must be developed. Here, we propose a fast and low-temperature synthesis method for metallic MoS2, which can be achieved on a flexible polyethylene terephthalate (PET) substrate. A precursor solution was prepared by a mixture of (NH4 )2 MoS4 powder and dimethylformamide. This solution was then coated on the silicon or PET substrate and an MoS2 film can be fabricated in unconstrained patterns such as lines or a continuous film at micro scale. The necessary laser power and exposure time were confirmed from systematic Raman spectroscopy measurements. The metallic behavior of the synthesized film was demonstrated by the electrical device fabrication and these excellent metallic properties show the feasibility of using MoS2 as a patternable electrode material on flexible substrates.